2022
DOI: 10.3389/fbioe.2022.875317
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of Ag/Quaternary Ammonium Salt Co-Decorated Mesoporous Silica Nanoparticles for Synergistic Treatment of Cancer and Bacterial Infections

Abstract: Developing drug delivery nanosystems with both anticancer and antibacterial effects is of great clinical value. Herein, we report a facile approach to synthesize Ag and quaternary ammonium salt (QAS) co-decorated mesoporous silica nanoparticles (MSNs), namely, Ag/QAS-MSNs, for synergistic treatment of cancer and bacterial infections. In vitro studies demonstrated that Ag/QAS-MSNs not only had a strong antibacterial activity against the bacterial pathogens but also could efficiently induce cancer cell death thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…For example, to enhance the efficacy of solo anti-tumour therapy, it was found that mesoporous silica nanoparticles (MSNs) co-modified with Ag and the quaternary ammonium salt (QAS) (Ag/QAS-MSNs) possessed an effective antimicrobial ability by adhering to negatively charged bacterial cell walls via electrostatic interactions and causing cell membrane damage. 69 Subsequently, the sustained release of Ag ions and the QAS from Ag/QAS-MSNs leads to the inhibition of bacterial growth via the apoptotic pathway and induction of tumour cell death in hepatocellular carcinoma (Fig. 2A).…”
Section: Drug Combined Delivery Systemsmentioning
confidence: 99%
“…For example, to enhance the efficacy of solo anti-tumour therapy, it was found that mesoporous silica nanoparticles (MSNs) co-modified with Ag and the quaternary ammonium salt (QAS) (Ag/QAS-MSNs) possessed an effective antimicrobial ability by adhering to negatively charged bacterial cell walls via electrostatic interactions and causing cell membrane damage. 69 Subsequently, the sustained release of Ag ions and the QAS from Ag/QAS-MSNs leads to the inhibition of bacterial growth via the apoptotic pathway and induction of tumour cell death in hepatocellular carcinoma (Fig. 2A).…”
Section: Drug Combined Delivery Systemsmentioning
confidence: 99%